. Changes in Serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and matrix metallopeptidase-2/9 (MMP-2/9), serum CD3+, CD4+, and CD8+ in patients undergoing thoracoscopic surgery for non-small-cell lung cancer: Serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and matrix metallopeptidase-2/9 (MMP-2/9), serum CD3+, CD4+, and CD8+ in patients undergoing thoracoscopic surgery - Zhang, Yannan (Journal of Medical Biochemistry, 2024)
AbstractObjective: Non-small-cell lung cancer (NSCLC) remains one of the most common malignancies worldwide, posing a great potential threat to the health and life safety of patients. Methods: One hundred and fifty NSCLC patients admitted to our hospital from September 2022 to September 2023 were selected, inflammatory response, changes in T-lymphocyte subpopulations before and after surgery were detected, and patients' psychological status was investigated. Finally, patients were followed up for 6 months to record the prognostic survival rate. Results: Postoperative inflammatory factors and CD8+ were lower in the research group than in the control group, while CD3, CD4+ and CD4/CD8+ were higher than in the control group (P0.05). Conclusion: Perioperative refinement of care can optimize the surgical process in patients with NSCLC, and the cellular immune function was enhanced.
Keywords: Non-small-cell lung cancer, Thoracoscopic surgery, Refined nursing, Inflammatory response, T lymphocyte subsets